Euthanasia spiritual, medical and legal issues in terminal health care - Spring, Beth; Larson, Ed (Portland, OR Multnomah, 1988)
Includes bibliographical references and index.
Keywords: Euthanasia -- religious aspects -- Christianity; Euthanasia -- moral and ethical aspects; Terminal care -- moral and ethical aspects